Transient Transformation of Oncidium Taka by Particle Bombardment - Wee, Chien Yeong (2006)
Oncidium Taka was used in this study for its importance as cut flower in Malaysia floriculture industry. Protocorm likes bodies (PLBs) that proved to have vigorous propagation and regeneration capacity were induced from shoot tips and flower buds in MS hormone free medium. Subsequently, callus induction by using different concentrations of auxins (2,4-D, dicamba, picloram, IAA and NAA) was investigated in dark condition. Picloram in a concentration of 40 μM was found to be the most effective for inducing callus from PLBs. However, the initiated callus was maintained and proliferated in medium consisted of combination hormones of 50 μM picloram and 20 μM kinetin. Both PLBs and callus were used as target tissues in the genetic transformation study.Regeneration study of these calli was carried out in half strength MS medium under light condition. The calli regenerated by intervening PLB stage and the shoot primordial was developed as early as 44 days after culture. Besides that, media composition and different concentrations of BAP were examined to enhance plant regeneration and plant growth from PLBs. Half strength MS medium supplemented with full strength B5 vitamin, 3 % sucrose and 20 μM BAP was found to be efficient for plant regeneration from PLBs. Apparently, better plant growth can be promoted in full strength MS medium supplemented with full strength B5 vitamin, 2 % sucrose and 20 μM BAP. The effectiveness of hygromycin as selective agents to inhibit growth of PLBs and callus was evaluated. Toxicity effect of hygromycin was found rapid and effective to kill the untransformed PLBs and callus in low concentration at 25 mg/L and 10 mg/L, respectively. GFP as a non-destructive, early and rapid detection reporter system was used in this transformation studies. The p35S-sgfp-TYG-nos GFP plasmid was determined to give the highest transient expression in both target tissues among five different plasmids evaluated. The fluorescent signals expressed with elevated level of green fluorescent on nuclei were observed using Leica Stereo-fluorescence System MZ FLIII with GFP 2 filter set that masked out chlorophyll. The highest numbers of transient expression achieved on day two postbombardment for both target tissues. The physical and biological parameters affecting DNA delivery, based on the highest scorable transient GFP expression and minimal tissue dislocation upon impact, were optimised. The physical parameters optimised in helium pressure, distance from stopping plate to target tissue, vacuum pressure, size of microcarrier, quantity of DNA and effect of CaCl2 and Spermidine were found no different between PLBs and callus. As for biological parameters tested, PLBs in sizes of 5 – 6 mm had significantly higher transient expression compared to calli. Seven days old calli with one day pre-culture period and fourteen days old PLBs that pre-culture on the same day gave the highest transient expression. The quantity of DNA per bombardment used was 1.5 μg for both target tissues to achieve the highest transient expression. The bombarded tissues were subsequently transferred to hygromycin containing medium for a minimum of six months selection. The survived and proliferated putative transformed tissues were subjected to molecular analysis. Insertion of the transgenes (gfp, gus A, hpt II and chs) into host genome was confirmed using PCR and Southern vi Blot analysis. Transformation efficiency was determined at 1.5 % to 1.67 % and 1.67 % to 2.5 % when using PLBs and callus, respectively as target tissue. In addition, PCR analysis showed co-transformation frequency of the un-linked genes from different plasmids was 40 % to 67 %.